ESTIMATION OF THERMAL CHARACTERISTICS LiFePO4 BATTERY SYSTEMS USING FINITE ELEMENT METHOD WITH EXPERIMENTAL DATA VALIDATION - Nugraha Rismi, Fadhlin
In the development of clean energy systems vehicles, such as hybrid electric vehicles and battery electric vehicles, batteries have an important role. A battery acts as an energy storage, which has the function of converting from chemical energy to electricity. One type of battery that is widely used is a cylindrical Lithium- ion battery with LiFePO4 type. Performance of battery system is affected by some factors, such as material components, temperature, charge-discharge current, and cycle life of battery. Thermal characteristic is one of the most investigated factors. In this study, thermal characteristics investigation was conducted at two stages: experimental stage and simulation and modeling stages. In the experimental stage, the batteries are configured 4 cells in series with a capacity of 14000mAh. In the experimental stage, batteries work at the discharge current C1, C2 and C4, with natural convection studies in insulation and non-insulation systems. The assumptions used in this study are the battery used has experienced more than 10 cycles, the radiation of heat from the battery is negligible, and the parameters and thermal constants are considered constant. The range of ambient temperature in operation is at 24oC-28,5oC. In battery system, generated heat comes from two processes, namely electrochemical reactions between electrodes and Joule heating. In the simulation and modeling stage, the finite element method is used. The finite element method is a method in which discretization is performed on the object to be analyzed, or by fragmenting the object into several elements. Each element is one with the other connected to the simpul. We built a mathematical equation that becomes a representation of the observed object. Simulations were performed using Comsol Multiphysics 5.2a. The research used finite element method to find the temperature distribution at battery. Experimental results indicate that battery systems in insulated condition have more stable thermal characteristics than non-insulated systems. In addition, in natural convection studies, the battery thermal measurements become heavily dependent on ambient temperatures seen in the overall temperature graph that illustrates the increase and decrease according to changes in ambient temperature. In this work, estimation we also made for insulation system with 10 batteries. The temperature rise characteristic shows the exponential graph of all simulations performed. By evaluating the measurement values in the experimental and simulation stages, non-insulation conditions achieve error value for the C1 discharging current of 1,77%, C2 of 1,97%, and C4 of 0,38%. Insulation conditions achieve error value for the C1 emptying current of 1,10%, C2 of 0,53%, and C4 of 0,05%.